Pedagogical Analysis of Social Skills in Colleges: Implications to Social Health - Ejifugha, Anthonia U. (Mediterranean Journal of Social Sciences, 2011)
Development of schools of thought in the concept of health yielded three dimensions of health: physical, psychologicaland social which fertilized the World Health Organization’s concept of health. Health education curricular particularly at thetertiary level has advanced the course of physical and psychological dimension of health to the negligence of social health.Advances in orthodox medicine, have established the scientific bases of social health. Health education curriculum outlines bythe National Commission of Colleges of Education (NCCE) ought to advance the course of social health. this is to emphasize itsrole in nation building particularly in averting many socially rooted or socially provoked health problems. The paper presents theneed for curriculum reform in health education in order to portray the need to interpersonal skills in social health education inNigeria. The first three levels of relationship: acquaintance, associate and friendship relationships were presented as the cornerstone of social skills from which other relational skills emanate. It is recommended that interpersonal skills should be presentedby teachers as core social health needs of students.